2018
DOI: 10.1016/j.neuron.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation of Attention

Abstract: Attention is critical to high-level cognition and attention deficits are a hallmark of neurologic and neuropsychiatric disorders. Although years of research indicates that distinct neuromodulators influence attentional control, a mechanistic account that traverses levels of analysis (cells, circuits, behavior) is missing. However, such an account is critical to guide the development of next-generation pharmacotherapies aimed at forestalling or remediating the global burden associated with disorders of attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
298
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(338 citation statements)
references
References 216 publications
13
298
1
Order By: Relevance
“…A previous study has shown that activation of the muscarinic receptors activates a calcium-sensitive, nonspecific cation current (Shalinsky, Magistretti, Ma, & Alonso, 2002) which induces persistent firing (Hasselmo & McGaughy, 2004). High levels of acetylcholine are also associated with attention, which is related to the change in cortical gain (summarized in Thiele & Bellgrove, 2018). We focused on changes in CAN current conductance because of this data on the effect of acetylcholine.…”
Section: Layer II Cells Also Decayed Exponentiallymentioning
confidence: 99%
“…A previous study has shown that activation of the muscarinic receptors activates a calcium-sensitive, nonspecific cation current (Shalinsky, Magistretti, Ma, & Alonso, 2002) which induces persistent firing (Hasselmo & McGaughy, 2004). High levels of acetylcholine are also associated with attention, which is related to the change in cortical gain (summarized in Thiele & Bellgrove, 2018). We focused on changes in CAN current conductance because of this data on the effect of acetylcholine.…”
Section: Layer II Cells Also Decayed Exponentiallymentioning
confidence: 99%
“…Various neurotransmitter systems are known to modulate attention (Thiele & Bellgrove, 2018). Here we focus on the catecholaminergic modulation of the interaction between perception and attention.…”
mentioning
confidence: 99%
“…In hippocampus, the functional consequences of this modality are long-lasting effects on synaptic connections (Adamsky et al, 2018;Navarrete et al, 2012), plausibly associated with memory formation. In cortex, we reason that astrocytic Ca 2+ rises, as reported by (Takata et al, 2011), participate in a well-accepted role of neuromodulation: Control of arousal and attention, which involves recruitment of large, spatially distributed neuronal populations (Thiele & Bellgrove, 2018). Importantly, the two modalities reveal the existence of threshold heterogeneity in Ca 2+ responses in astrocytes, which might be of computational importance.…”
Section: Existence Of Short-and Long-term Modalities In Ca 2+ Respomentioning
confidence: 89%
“…Neuromodulation refers to the relatively rapid (in the range of seconds) functional reconfiguration of circuits throughout the brain by acetylcholine, dopamine, noradrenaline, and serotonin, which are released by subcortical and brainstem nuclei: The nucleus basalis of Meynert (NBM), the striatum, the locus coeruleus, and the Raphe nucleus (Avery & Krichmar, 2017). Neuromodulation participates in working memory, attention, brain state, and plasticity (Meunier, Chameau, & Fossier, 2017;Sara, 2009;Thiele & Bellgrove, 2018).…”
Section: Computation Takes Place At Several Hierarchically Organizementioning
confidence: 99%